Comparison of effects of intraoperative nefopam and ketamine infusion on managing postoperative pain after laparoscopic cholecystectomy administered remifentanil - Sung Kwan Choi; Myung Ha Yoon; Jung Il Choi; Woong Mo Kim; Bong Ha Heo; Keun Seok Park; Ji A Song (Korean Journal of Anesthesiology, 2016)
BackgroundAlthough intraoperative opioids provide more comfortable anesthesia and reduce the use of postoperative analgesics, it may cause opioid induced hyperalgesia (OIH). OIH is an increased pain response to opioids and it may be associated with N-methyl-D-aspartate (NMDA) receptor. This study aimed to determine whether intraoperative nefopam or ketamine, known being related on NMDA receptor, affects postoperative pain and OIH after continuous infusion of intraoperative remifentanil.MethodsFifty-four patients undergoing laparoscopic cholecystectomy were randomized into three groups. In the nefopam group (N group), patients received nefopam 0.3 mg/kg at the induction of anesthesia followed by a continuous infusion of 0.065 mg/kg/h. In the ketamine group (K group), patients received ketamine 0.3 mg/kg at the induction of anesthesia followed by a continuous infusion of 3 µg/kg/min. The control group did not received any other agents except for the standard anesthetic regimen. Postoperative pain score, first time and number of demanding rescue analgesia, OIH and degrees of drowsiness/sedation scale were examined.ResultsCo-administrated nefopam or ketamine significantly reduced the total amount of intraoperative remifentanil and postoperative supplemental morphine. Nefopam group showed superior property over control and ketamine group in the postoperative VAS score and recovery index (alertness and respiratory drive), respectively. Nefopam group showed lower morphine consumption than ketamine group, but not significant.ConclusionsBoth nefopam and ketamine infusion may be useful in managing in postoperative pain control under concomitant infusion of remifentanil. However, nefopam may be preferred to ketamine in terms of sedation.